TRIM50 Suppresses Pancreatic Cancer Progression and Reverses the Epithelial-Mesenchymal Transition via Facilitating the Ubiquitous Degradation of Snail1 - Li, Rongkun; Zhu, Lili; Peng, Yangxizi; Zhang, Xiaoxin; Dai, Chunhua; Liu, Dejun (Frontiers in Oncology, 2021)
Emerging evidence suggests that the tripartite motif (TRIM) family play important roles in tumor development and progression. Tripartite motif-containing 50 (TRIM50) is a member of the TRIM family, but little is known regarding its expression and potential functional roles in cancer. In this study, we first analyzed the expression pattern and clinical significance of TRIM50 in pancreatic cancer and found that TRIM50 expression is significantly reduced in pancreatic cancer tissues and its downregulation is associated with poor survival for pancreatic cancer patients. Functionally, TRIM50 overexpression in pancreatic cancer cells decreases their proliferation and motility capabilities and reverses the epithelial-mesenchymal transition (EMT) process, whereas TRIM50 depletion had the opposite effects. Mechanically, TRIM50 directly interacts with Snail1, a key regulator of EMT, and acts as an E3 ubiquitin ligase to target Snail1 for ubiquitous degradation. The function of TRIM50 in suppressing cell migration and EMT depends on TRIM50-promoted Snail1 degradation. In conclusion, our findings identify TRIM50 as a tumor suppressor that inhibits pancreatic cancer progression and reverses EMT via degrading Snail1 and provide new insights into the progression of pancreatic cancer.